2017
DOI: 10.4102/ojvr.v84i1.1445
|View full text |Cite
|
Sign up to set email alerts
|

The sero-prevalence and sero-incidence of African horse sickness and equine encephalosis in selected horse and donkey populations in Zimbabwe

Abstract: Sentinel herds and samples submitted by private equine practitioners were used to determine the sero-prevalence and sero-incidence of African horse sickness virus (AHSV) and equine encephalosis virus (EEV) in horse and donkey populations in the Highveld region of Zimbabwe. The sero-prevalence and sero-incidence of antibodies against these viruses were determined using the competitive enzyme-linked immunosorbent assay (ELISA) for the detection of serum antibodies. In donkeys, the median sero-prevalence of AHSV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
1
13
1
1
Order By: Relevance
“…This survey indicated that the majority of Namibian donkeys (63.5%) had been exposed to AHSV. The results of the current study are in agreement with studies from other African countries that have reported donkey AHSV prevalence of between 59.3% and 72% [9,10]. It would appear that all AHSV serotypes, except AHSV-8, occur in Namibia.…”
Section: Discussionsupporting
confidence: 92%
“…This survey indicated that the majority of Namibian donkeys (63.5%) had been exposed to AHSV. The results of the current study are in agreement with studies from other African countries that have reported donkey AHSV prevalence of between 59.3% and 72% [9,10]. It would appear that all AHSV serotypes, except AHSV-8, occur in Namibia.…”
Section: Discussionsupporting
confidence: 92%
“…En Ethiopie, une étude montre ainsi une séroprévalence plus élevée chez les ânes (51,1 %) que chez les chevaux (28,3 %) (Bitew et al, 2011). Nos résultats confortent ceux obtenus par Gordon et al (2017). En général, la séroprévalence importante régulièrement observée chez l'âne confirme le rôle que jouerait cette espèce dans la circulation du virus de la PEA en intervenant comme un réservoir (Hamblin et al, 1998).…”
Section: ■ Discussionunclassified
“…The chance of isolating free virus was improved by assaying the blood samples collected before animals seroconverted. Virus isolations were made by intravenous inoculation of 11-day-old embryonated hens’ eggs (IAH, UK) and by intracerebral inoculation of 1- to 2-day-old suckling mice (CD-1, UK) using techniques described by Gordon et al ( 2017 ). The viruses isolated were typed using virus type-specific antisera and BHK-21 cells in microtitre plates using neutralisation test methods modified from Hazrati and Ozawa ( 1965 ).…”
Section: Methodsmentioning
confidence: 99%